The transport properties of Kekulé-ordered graphene p–n junction - Peipei Zhang; Chao Wang; Yu-Xian Li; Lixue Zhai; Juntao Song (New Journal of Physics, 2023)
The transport properties of electrons in graphene p – n junction with uniform Kekulé lattice distortion have been studied using the tight-binding model and the Landauer–Büttiker formalism combined with the nonequilibrium Green’s function method. In the Kekulé-ordered graphene, the original K and K ʹ valleys of the pristine graphene are folded together due to the $\sqrt{3} × \sqrt{3}$ enlargement of the primitive cell. When the chiral symmetry breaking of a valley leads to a single-valley phase, there are special transport properties of Dirac electrons in the Kekulé lattice. In the O-shaped Kekulé graphene p – n junction, Klein tunneling is suppressed, and only resonance tunneling occurs. In the Y-shaped Kekulé graphene p – n junction, the transport of electrons is dominated by Klein tunneling. When the on-site energy modification is introduced into the Y-shaped Kekulé structure, both Klein tunneling and resonance tunneling occur, and the electron tunneling is enhanced. Under strong magnetic fields, the conductance of O-shaped and on-site energy-modified Y-shaped Kekulé graphene p – n junctions is non-zero due to the presence of resonance tunneling. It is also found that the disorder can enhance conductance, with conductance plateaus forming in the appropriate range of disorder strength.